2015
DOI: 10.1007/s00394-015-0834-0
|View full text |Cite
|
Sign up to set email alerts
|

Mice fed fish oil diet and upregulation of brown adipose tissue thermogenic markers

Abstract: FO improves metabolic profile and upregulates thermogenic markers, suggesting an elevated thermogenesis that leads to reduced BM gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 41 publications
14
85
1
Order By: Relevance
“…6G) were confirmed in iBAT from HF ϩ FO-fed mice compared with HF ϩ PO-or HF ϩ OO-fed mice. These results are consistent with recent publications showing thermogenic activation with FO supplementation (6,7). Subsequently, we analyzed the five candidate miRNAs that were up-regulated with EPA treatment in vitro; all five miRNAs, miR-30b, miR-193b, miR-365, miR-196a, and miR-378, were significantly up-regulated in iBAT from mice fed a HF ϩ FO diet compared with HF ϩ OO-or HF ϩ PO diet-fed mice (Fig.…”
Section: Epa Promotes Brown Adipogenesis By Altering Mirnasupporting
confidence: 94%
See 1 more Smart Citation
“…6G) were confirmed in iBAT from HF ϩ FO-fed mice compared with HF ϩ PO-or HF ϩ OO-fed mice. These results are consistent with recent publications showing thermogenic activation with FO supplementation (6,7). Subsequently, we analyzed the five candidate miRNAs that were up-regulated with EPA treatment in vitro; all five miRNAs, miR-30b, miR-193b, miR-365, miR-196a, and miR-378, were significantly up-regulated in iBAT from mice fed a HF ϩ FO diet compared with HF ϩ OO-or HF ϩ PO diet-fed mice (Fig.…”
Section: Epa Promotes Brown Adipogenesis By Altering Mirnasupporting
confidence: 94%
“…Despite the surge of research for identifying cellular and molecular regulators of brown fat development (2,3), the role of dietary constituents, particularly dietary fatty acids (FA), in thermogenic activation is poorly understood. Depending on the degree of desaturation and the n-6/n-3 ratio, FA differentially control adiposity, insulin sensitivity, immune response (4), and probably energy expenditure (5)(6)(7). Lately, it has been suggested that n-3 polyunsaturated FA (PUFA) stimulate beige/brown adipogenesis in primary murine adipogenic precursor cells (5) as well as C57BL/6 mice (6, 7).…”
mentioning
confidence: 99%
“…Secondly, these fatty acids also elevate fatty acid oxidation in the liver [23] and small intestine [24]. Besides that, it was also demonstrated that a diet rich in fish oil can increase uncoupling protein 1 in brown adipose tissue, suggesting elevated thermogenesis [25]. All these conditions can justify the diminished BM gain in the HF-FO group.…”
Section: Discussionmentioning
confidence: 96%
“…CPT-1 upregulation is well-known to play a role in obesity alleviation (Rameshreddy et al, 2018). Upregulation of both genes may be also linked to enhanced lipolysis and decreased TGs level, where the released free fatty acids are transported to the mitochondria via the activated CPT-1 enzyme, with simultaneous induction of the thermogenic activity of UCP-1 (Bargut et al, 2016). UCP-1 is known to mediate diet-induced adrenergic thermogenesis, where its ablation was found to induce obesity (Feldmann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Uncoupling protein-1 (UCP-1) is expressed mainly by the brown adipose tissues. UCP-1 is sited within the inner mitochondrial membrane where it increases energy dissipation via uncoupling of mitochondrial oxidation of substrates producing heat instead of ATP (Bargut et al, 2016). Carnitine palmitoyl transferase-1 (CPT-1) is sited at the outer membrane of the mitochondria and it is the rate-determining step in fatty acid β-oxidation.…”
Section: Introductionmentioning
confidence: 99%